Method for preparing Prussian blue positive electrode material through carbon coating
By forming an in-situ carbon cladding on the Prussian blue positive electrode material, the problem of easy structure destruction of the material during the electrochemical cycle is solved, and its electrochemical performance and stability are significantly improved.
Patent Information
- Application Number
- CN202411457183.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-18
AI Technical Summary
The existing Prussian blue cathode material is easily damaged during the electrochemical cycle, resulting in poor electrochemical performance, and it is difficult for existing improvement methods to effectively improve its performance.
By using the carbon coating method, commercial Prussian blue is heat treated under an inert atmosphere to form an in situ carbon coating layer to improve the structural stability and electron conductivity of the material.
It significantly improves the electron conductivity and structural stability of Prussian Blue, and improves its cycling performance and capacity retention in electrochemical cycles.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of novel sodium ion battery positive electrode materials, and specifically relates to a method for preparing a Prussian blue positive electrode material by carbon coating. Background Art
[0002] Prussian blue has an open framework and a stable structure. Its preparation method is simple and reliable. Its theoretical discharge capacity can reach 170 mAh / g. It is a highly potential cathode material for sodium ion batteries. However, the structure of iron-based Prussian blue materials is easily destroyed during the electrochemical cycle, resulting in poor electrochemical performance of the material. Therefore, many researchers have used various methods to improve its electrochemical performance.
[0003] Patent CN118419950A discloses a simple preparation method for high-quality Prussian blue compounds (PB) and their analogs (PBA) for the positive electrode of sodium ion batteries, which mainly includes the following steps: introducing anhydrous ethanol to dissolve manganese acetate, and slowly dripping it dropwise into a sodium ferrocyanide solution under stirring conditions, and controlling a certain aging temperature and time, and obtaining the product by centrifugal washing and drying.
[0004] Patent CN118439630A discloses a Prussian blue cathode material and a preparation method and application thereof; the preparation method comprises the following steps: S1, weighing an appropriate amount of a chelating agent and dissolving it in a ferric chloride solution to obtain a first mixed solution; S2, weighing an appropriate amount of sodium ferrocyanide decahydrate and dissolving it in a saturated sodium chloride solution to obtain a second mixed solution; S3, freezing and crushing the first mixed solution and the second mixed solution in turn to obtain a first powder and a second powder; S4, mixing the first powder and the second powder in a low temperature environment, stirring the reaction under the protection of an inert gas and centrifuging; S5, washing and freeze-drying the precipitate obtained by centrifugation to obtain a Prussian blue cathode material.
[0005] However, existing research is still not enough to improve its electrochemical performance. Carbon coating as a composite coating method can improve the structural stability of the material during the electrochemical cycle. Since Prussian blue decomposes when heated and the decomposition temperature is low, it begins to decompose at 300°C. The commonly used high-temperature carbon coating method is difficult to apply to Prussian blue. Usually, Prussian blue and carbon are mixed by ball milling or liquid phase, and carbon is directly coated on the surface of Prussian blue particles to improve its electrochemical performance. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a Prussian blue positive electrode material by carbon coating, wherein commercial Prussian blue is heat-treated under an inert atmosphere, and through subsequent experiments, the material obtained by the heat treatment at a specific temperature is synthesized into an in-situ carbon-coated Prussian blue.
[0007] The technical solution of the present invention is: a method for preparing a Prussian blue positive electrode material by carbon coating, comprising the following steps:
[0008] A. A commercial Prussian blue material (Fe4[Fe(CN)6]3) is heat-treated in a N2 atmosphere to serve as a precursor sample. Sodium ferrous decahydrate, N-methyl-2-pyrrolidone (NMP) and acetic acid are added to the heat-treated sample, and the mixture is placed in a ball mill, and ball-milled on a planetary ball mill. The ball-milled mixture is then placed in a beaker containing deionized water and stirred, and then washed with a detergent to obtain an insoluble substance, which is then vacuum-dried to obtain a carbon-coated Prussian blue.
[0009] B. Assemble the battery and test its discharge capacity and cycle performance at a current density of 1C.
[0010] As a preferred technical solution of the present invention, in step A, the calcination temperature is 500-650°C.
[0011] As a preferred technical solution of the present invention, in step A, the heating rate is 10°C / min and the insulation time is 1h.
[0012] As a preferred technical solution of the present invention, in step A, the molar ratio of sodium ferrous decahydrate, N-methyl-2-pyrrolidone (NMP) and acetic acid is 0.1-0.3:1-3:0-0.0875.
[0013] As a preferred technical solution of the present invention, in step A, the planetary ball mill is operated at a speed of 250 rpm for 1-3 hours.
[0014] As a preferred technical solution of the present invention, in step A, the ball-milled mixture is placed in a beaker containing deionized water and stirred for 0.5-2h.
[0015] As a preferred technical solution of the present invention, in step A, the detergent is one or both of deionized water and anhydrous ethanol.
[0016] As a preferred technical solution of the present invention, in step A, the washing times are 2-5 times.
[0017] As a preferred technical solution of the present invention, in step A, the insoluble matter is dried in a vacuum oven at 50-100° C. for 6-24 hours.
[0018] As a preferred technical solution of the present invention, in step A, the preparation method of N-methyl-2-pyrrolidone (ionic liquid active agent) is:
[0019] In a stainless steel reaction kettle with a stirring and heating device, nitrogen is introduced to replace air, and then 1000-1500 parts of ethanol, 5-10 parts of sodium hydroxide, 0.5-1 part of 1-allyl-3-methylimidazolium tetrafluoroborate, and 0.01-0.3 part of 5-amino-3-bromobenzonitrile are added, the temperature is raised to 60-70°C, and the reaction is carried out for 120-180 minutes. Then, 0.4-0.8 parts of 3-amino-2-pyrrolidone are added, the temperature is raised to 60-70°C, and the reaction is carried out for 60-100 minutes. Then, the ethanol is removed by evaporation under reduced pressure to obtain an ionic liquid active agent.
[0020] Reaction mechanism:
[0021] 1. The addition of NMP reagent is mainly used to dissolve acetic acid. During the ball milling process, under the action of acetic acid, sodium ferrocyanide will react with the precursor sample, and finally a blue mixture will be obtained in the ball tank.
[0022] 2. In an inert gas, commercial Prussian blue can obtain the intermediate phase Fe2[Fe(CN)6] after heat treatment, and form carbon coating in situ. The intermediate phase Fe2[Fe(CN)6] is the key to the subsequent formation of Prussian blue. In addition, as the heat treatment temperature increases, the higher the degree of graphitization of carbon, the better the conductivity of carbon-coated Prussian blue. When the temperature exceeds 600°C, Fe2[Fe(CN)6] will decompose to form Fe and FexC, and Prussian blue cannot be synthesized.
[0023] 3. Amino-allyl addition reaction: 5-amino-3-bromobenzonitrile and 1-allyl-3-methylimidazolium tetrafluoroborate form new compounds through amino-allyl addition reaction. This step is one of the key reactions for the formation of pyrrolidone containing tetrafluoroborate / benzonitrile.
[0024] 4. Addition reaction of 3-amino-2-pyrrolidone and 1-allyl-3-methylimidazolium tetrafluoroborate:
[0025] 3-Amino-2-pyrrolidone also reacted with 1-allyl-3-methylimidazolium tetrafluoroborate via an amino-allyl addition reaction, further enriching the structure and properties of the final product.
[0026] 5. In-situ carbon coating process:
[0027] Transformation of precursor materials at high temperatures: Under high temperature conditions, the organic components in the precursor materials decompose and form a carbon layer on the surface of Prussian blue. These carbon atoms are uniformly deposited on the surface of Prussian blue materials to form a continuous and uniform carbon layer.
[0028] Technical Effects
[0029] 1. Improve electrical conductivity:
[0030] The uniform and dense carbon coating formed on the surface of Prussian blue significantly improves the electronic conductivity of the material. This is because the carbon layer acts as a conductive medium and enhances the electron transmission ability between particles.
[0031] 2. Enhance structural stability:
[0032] The uniform carbon layer not only enhances the structural strength of Prussian blue, but also inhibits the shedding of active substances during electrochemical reactions to a certain extent, thus ensuring the cycle stability of the electrode material.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] A new method for high-temperature in-situ carbon coating of Prussian blue has been designed. The coating layer obtained by this method is more uniform and dense. The carbon coating can improve the electronic conductivity of Prussian blue and enhance its structural stability during electrochemical cycles. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with specific implementation modes.
[0036] Embodiment 1,
[0037] A method for preparing a Prussian blue positive electrode material by carbon coating, comprising the following steps:
[0038] A. The commercial Prussian blue material (Fe4[Fe(CN)6]3) was heated to 560℃ in N2 atmosphere at a heating rate of 10℃ / min and heat treated for 1h. This was the precursor sample. 96.81g of sodium ferrous decahydrate, 200mL of N-methyl-2-pyrrolidone (NMP) and 2.5ml of acetic acid were added to the heat-treated sample, mixed and put into a ball mill, and ball milled on a planetary ball mill at a speed of 250rpm for 2h. The ball-milled mixture was then placed in a beaker containing deionized water and stirred for 1h. Then, it was washed with deionized water and anhydrous ethanol by centrifugation for 3 times to obtain insoluble matter. The insoluble matter was dried in a vacuum oven at 80℃ for 12h to obtain carbon-coated Prussian blue.
[0039] The preparation method of the N-methyl-2-pyrrolidone (ionic liquid active agent) is:
[0040] In a stainless steel reaction kettle with a stirring and heating device, nitrogen was introduced to replace the air, and then 1300 mL of ethanol, 280 g of sodium hydroxide, 159 g of 1-allyl-3-methylimidazolium tetrafluoroborate, and 29.55 g of 5-amino-3-bromobenzonitrile were added, the temperature was raised to 65° C., and the reaction was carried out for 150 minutes. Then, 60 g of 3-amino-2-pyrrolidone (100.12) was added, the temperature was raised to 65° C., and the reaction was carried out for 80 minutes. Then, the ethanol was removed by evaporation under reduced pressure to obtain an ionic liquid active agent.
[0041] B. The battery was assembled and tested to have a discharge capacity of 123.5 mAh / g at a current density of 1 C. The capacity retention rate after 300 cycles was 80%.
[0042] Embodiment 2,
[0043] A method for preparing a Prussian blue positive electrode material by carbon coating, comprising the following steps:
[0044] A. The commercial Prussian blue material (Fe4[Fe(CN)6]3) was heated to 500℃ in N2 atmosphere at a heating rate of 8℃ / min and heat treated for 1h. This was the precursor sample. 48.4g of sodium ferrous decahydrate and 100mL of N-methyl-2-pyrrolidone (NMP) were added to the heat-treated sample, and the mixture was put into a ball mill. The mixture was ball milled on a planetary ball mill at a speed of 250rpm for 1h. The ball-milled mixture was then placed in a beaker containing deionized water and stirred for 0.5h. Then, the mixture was washed twice by centrifugation with deionized water and anhydrous ethanol respectively to obtain insoluble matter. The insoluble matter was dried in a vacuum oven at 50℃ for 6h to obtain carbon-coated Prussian blue.
[0045] The preparation method of the N-methyl-2-pyrrolidone (ionic liquid active agent) is:
[0046] In a stainless steel reaction kettle equipped with a stirring and heating device, nitrogen was introduced to replace the air, and then 1000 mL of ethanol, 200 g of sodium hydroxide, 106 g of 1-allyl-3-methylimidazolium tetrafluoroborate (212), and 1.97 g of 5-amino-3-bromobenzonitrile (197.03) were added, the temperature was raised to 60° C., and the reaction was continued for 120 minutes. Then, 40 g of 3-amino-2-pyrrolidine was added, the temperature was raised to 60° C., and the reaction was continued for 60 minutes. Then, the ethanol was removed by evaporation under reduced pressure to obtain an ionic liquid active agent.
[0047] B. The battery was assembled and tested to have a discharge capacity of 117.4 mAh / g at a current density of 1 C. The capacity retention rate after 300 cycles was 78.5%.
[0048] Embodiment 3,
[0049] A method for preparing a Prussian blue positive electrode material by carbon coating, comprising the following steps:
[0050] A. The commercial Prussian blue material (Fe4[Fe(CN)6]3) was heated to 650℃ in N2 atmosphere at a heating rate of 12℃ / min and heat treated for 1h. This was the precursor sample. 145.22g of sodium ferrous decahydrate, 300mL of N-methyl-2-pyrrolidone (NMP) and 5mL of the heat-treated sample were added, mixed and put into a ball mill, and ball milled on a planetary ball mill at a speed of 250rpm for 3h. The ball-milled mixture was then placed in a beaker containing deionized water and stirred for 2h. Then, it was washed with deionized water and anhydrous ethanol by centrifugation for 5 times to obtain insoluble matter. The insoluble matter was dried in a vacuum oven at 100℃ for 24h to obtain carbon-coated Prussian blue.
[0051] The preparation method of the N-methyl-2-pyrrolidone (ionic liquid active agent) is:
[0052] In a stainless steel reactor with a stirring and heating device, nitrogen was introduced to replace the air, and then 1500 mL of ethanol, 400 g of sodium hydroxide, 212 g of 1-allyl-3-methylimidazolium tetrafluoroborate, and 59.1 g of 5-amino-3-bromobenzonitrile were added, the temperature was raised to 70° C., and the reaction was carried out for 180 minutes. Then, 80 g of 3-amino-2-pyrrolidone (100.12) was added, the temperature was raised to 70° C., and the reaction was carried out for 100 minutes. Then, the ethanol was removed by evaporation under reduced pressure to obtain an ionic liquid active agent.
[0053] B. The battery was assembled and tested to have a discharge capacity of 109.3 mAh / g at a current density of 1 C. The capacity retention rate after 300 cycles was 70.8%.
[0054] Comparative Example 1
[0055] A method for preparing a Prussian blue positive electrode material by carbon coating, comprising the following steps:
[0056] A. The commercial Prussian blue material (Fe4[Fe(CN)6]3) was heated to 560℃ in N2 atmosphere at a heating rate of 10℃ / min and heat treated for 1h. This was the precursor sample. 96.81g of sodium ferrous decahydrate, 200mL of N-methyl-2-pyrrolidone (NMP) and 2.5ml of acetic acid were added to the heat-treated sample, mixed and put into a ball mill, and ball milled on a planetary ball mill at a speed of 250rpm for 2h. The ball-milled mixture was then placed in a beaker containing deionized water and stirred for 1h. Then, it was washed with deionized water and anhydrous ethanol by centrifugation for 3 times to obtain insoluble matter. The insoluble matter was dried in a vacuum oven at 80℃ for 12h to obtain carbon-coated Prussian blue.
[0057] B. The battery was assembled and tested to have a discharge capacity of 102.1 mAh / g at a current density of 1 C. The capacity retention rate after 300 cycles was 63.5%.
Claims
1. A method for preparing a Prussian blue positive electrode material by carbon coating, characterized in that The following steps are involved: A. A commercial Prussian blue material (Fe4[Fe(CN)6]3) is heat-treated in a N2 atmosphere to serve as a precursor sample. Sodium ferrous decahydrate, N-methyl-2-pyrrolidone (NMP) and acetic acid are added to the heat-treated sample, and the mixture is placed in a ball mill, and ball-milled on a planetary ball mill. The ball-milled mixture is then placed in a beaker containing deionized water and stirred, and then washed with a detergent to obtain an insoluble substance, which is then vacuum-dried to obtain a carbon-coated Prussian blue. B. Assemble the battery and test its discharge capacity and cycle performance at a current density of 1C.
2. The method for preparing a Prussian blue positive electrode material by carbon coating according to claim 1, characterized in that: In step A, the calcination temperature is between 500 and 650°C.
3. The method for preparing a Prussian blue positive electrode material by carbon coating according to claim 1, characterized in that: In step A, the heating rate is 10°C / min and the holding time is 1h.
4. The method for preparing a Prussian blue positive electrode material by carbon coating according to claim 1, characterized in that: In step A, the molar ratio of sodium ferrous decahydrate, N-methyl-2-pyrrolidone (NMP) and acetic acid is 0.1-0.3:1-3:0-0.0875.
5. The method for preparing a Prussian blue positive electrode material by carbon coating according to claim 1, characterized in that: In step A, the planetary ball mill is operated at a speed of 250 rpm for 1-3 h.
6. The method for preparing a Prussian blue positive electrode material by carbon coating according to claim 1, characterized in that: In step A, the ball-milled mixture is placed in a beaker containing deionized water and stirred for 0.5-2 hours.
7. The method for preparing a Prussian blue positive electrode material by carbon coating according to claim 1, characterized in that: In step A, the detergent is one or both of deionized water and anhydrous ethanol.
8. The method for preparing a Prussian blue positive electrode material by carbon coating according to claim 1, characterized in that: In step A, the washing times are 2-5 times.
9. The method for preparing a Prussian blue positive electrode material by carbon coating according to claim 1, characterized in that: In step A, the insoluble matter is dried in a vacuum oven at 50-100° C. for 6-24 hours.
10. The method for preparing a Prussian blue positive electrode material by carbon coating according to claim 1, characterized in that: In step A, the preparation method of N-methyl-2-pyrrolidone (ionic liquid active agent) is: In a stainless steel reaction kettle with a stirring and heating device, nitrogen is introduced to replace air, and then 1000-1500 parts of ethanol, 5-10 parts of sodium hydroxide, 0.5-1 part of 1-allyl-3-methylimidazolium tetrafluoroborate, and 0.01-0.3 part of 5-amino-3-bromobenzonitrile are added, the temperature is raised to 60-70°C, and the reaction is carried out for 120-180 minutes. Then, 0.4-0.8 parts of 3-amino-2-pyrrolidone are added, the temperature is raised to 60-70°C, and the reaction is carried out for 60-100 minutes. Then, the ethanol is removed by evaporation under reduced pressure to obtain an ionic liquid active agent.